2022
DOI: 10.1002/adma.202203309
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Polymer Nanoparticles with Surface‐Mimicking Protein Secondary Structure as Lysosome‐Targeting Chimaeras for Self‐Synergistic Cancer Immunotherapy

Abstract: Immunotherapy has received tremendous attention for tumor treatment, but the efficacy is greatly hindered by insufficient tumor‐infiltration of immune cells and immunosuppressive tumor microenvironment. The strategy that can efficiently activate cytotoxic T lymphocytes and inhibit negative immune regulators will greatly amplify immunotherapy outcome, which is however very rare. Herein, a new kind of semiconducting polymer (SP) nanoparticles is developed, featured with surface‐mimicking protein secondary struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 100 publications
1
44
0
Order By: Relevance
“…It is therefore meaningful to investigate the combination of PTT/PDT and other immunotherapeutic agents, like immune checkpoint inhibitors, to achieve the best immunological activation against cancer and potentiate the abscopal effect of the treatment [ 96 ]. PTT and PDT treatments are amongst the treatments that induce immunogenic cancer cell death, leading to priming and activation of the immune system against the tumor [ 134 , [260] , [261] , [262] , [263] , [264] ].…”
Section: Pt-based Combinatory Cancer Therapymentioning
confidence: 99%
“…It is therefore meaningful to investigate the combination of PTT/PDT and other immunotherapeutic agents, like immune checkpoint inhibitors, to achieve the best immunological activation against cancer and potentiate the abscopal effect of the treatment [ 96 ]. PTT and PDT treatments are amongst the treatments that induce immunogenic cancer cell death, leading to priming and activation of the immune system against the tumor [ 134 , [260] , [261] , [262] , [263] , [264] ].…”
Section: Pt-based Combinatory Cancer Therapymentioning
confidence: 99%
“… 136 Based on this, Ding et al constructed a new kind of semiconducting polymer (SPSS NPs) which worked along double lines, enhanced the photosensitization by organic semiconducting polymer SP3, and activated cytotoxic T lymphocytes to amplify immunotherapy by β-sheet protein degrading PD-L1 ( Figure 11 A). 137 Unlike traditional ICB therapy, this brand-new approach avoiding some potential problems such as high cost, difficulty for storage, high risk of immunogenicity, and short half-life in biological systems further guarantees its application in IPDT. The experimental results indicated that SPSS NPs can not only produce high-level ROS but also elicit strong ICD to release DAMPs, which could evoke long-term immunological memory against tumor rechallenge.…”
Section: Organic Photosensitizers Used For Ipdtmentioning
confidence: 99%
“… (A) Schematic illustration of SPSS NPs for self-synergistic cancer immunotherapy and its chemical structure. Reproduced from ref ( 137 ). Copyright 2022 Wiley-VCH.…”
Section: Organic Photosensitizers Used For Ipdtmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a clinically used method for treating some cancers, which is based on a light-triggered photosensitizer to generate ROS, especially the highly toxic 1 O 2 [ 135 , 136 , 137 ]. To monitor the in situ generation of 1 O 2 during PDT in real time is of comparative significance for tumor therapy and reduced side effects.…”
Section: Detection Of Reactive Oxygen Nitrogen Speciesmentioning
confidence: 99%